1996
DOI: 10.1007/s001250050512
|View full text |Cite
|
Sign up to set email alerts
|

Expression of nitric oxide synthase in macula densa in streptozotocin diabetic rats

Abstract: Renal haemodynamic changes are suggested to be an early sign of diabetic glomerulopathy. The juxtaglomerular apparatus relevant to the renin angiotensin system, known to be the site of nitric oxide (NO) production, is considered to play a role in the regulation of glomerular blood flow. This study was therefore designed to clarify whether in situ expression of nitric oxide synthase (NOS) is altered in the kidney of diabetic rats. Streptozotocin-induced diabetic rats with 6, 8, 12 and 32 weeks diabetes duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 48 publications
2
23
2
Order By: Relevance
“…To the best of our knowledge, several previous studies have explored nNOS renalexpression in diabetes. Supporting our findings, Yagihashi et al [30] reported less intense immunohistochemical staining for cyclic NOS (presumably nNOS) in MD and glomerular arterioles in rats with various durations of diabetes. In contrast, Choi et al [31] and Komers et al [17] found a marked increase in cortical nNOS in STZ-diabetic rats, as assessed by Western blotting and immunohistochemistry, respectively.…”
Section: Discussionsupporting
confidence: 77%
“…To the best of our knowledge, several previous studies have explored nNOS renalexpression in diabetes. Supporting our findings, Yagihashi et al [30] reported less intense immunohistochemical staining for cyclic NOS (presumably nNOS) in MD and glomerular arterioles in rats with various durations of diabetes. In contrast, Choi et al [31] and Komers et al [17] found a marked increase in cortical nNOS in STZ-diabetic rats, as assessed by Western blotting and immunohistochemistry, respectively.…”
Section: Discussionsupporting
confidence: 77%
“…Yagihashi et al 16 showed decreased immunoreactivity of nNOS in the macula densa and glomerular arterioles in diabetic rats. Similarly, in another study, it was shown that kidney nNOS activity decreased and protein levels were significantly lowered in STZ diabetic animals.…”
Section: Discussionmentioning
confidence: 97%
“…Diaphorase staining and immunohistochemical staining suggest reduced NOS activity in sympathetic autonomic ganglia 165 and macula densa 166 of experimental diabetic rats. Another study revealed a decrease in mRNA and content of neuronal NOS (nNOS) in diabetic penile tissue.…”
Section: Measurement Of Nos Protein Mrna or Activitymentioning
confidence: 91%